Tourism Destination Image: Towards a Conceptual Framework - Ahmad Puad, Mat Som; Wan Abd Aziz, Wan Mohd Amin; Norsuhaily, Abu Bakar; Nik Yusnita, Nik Ahmed (2018)
The growth of tourism industry in the century has provided travellers with the opportunity to choose a variety of destinations that have been developed with a variety of options that are available and continue to grow. Additionally, the technology available today has provided visitors with pleasure in a short time. Among them are the efficient transport network, high income, plenty of free time and so on. Selection of tourist destinations based on promotions is very important to tourists who want to travel. The destination is to have a clear distinction either from its competition, its positive position and an interesting place or destination image. Destination images are an important attraction to tourism development. Destinations with positive images are more likely to be considered and chosen as a starting point for travel. Destination images play an important role in determining travel direction for tourists for satisfaction and for marketing strategies for industry parties.